FIGURES OF SPEECH IN SURAH AR-RAHMAN - Ainun Rida Nasution; Sumarsih Sumarsih; Amrin Saragih (LINGUISTIK TERAPAN, 2018)
The aims of this study were to find out the kinds of figures of speech in surah Ar-Rahman, and to investigate realization of figures of speech in surah Ar-Rahman. The research was conducted by using qualitative descriptive design. The data of this study were 78 verses of surah Ar –Rahman. Besides, Miles, Huberman’s, and Saldana’s analysis applied in this study. In addition, Keraf theory (2004) was used in this study to find out kinds of figures of speech in surah Ar-Rahman, and Arp and Perrine theory (1963) was applied to investigate realization of figures of speech in surah Ar-rahman. The results of this study were (1) There were 10 kinds figures of speech in surah Ar-Rahman namely 3 Simile 2 Personifications 1 Apophasis 31 Repetition 2 Paralellism 1 Apostrophe  2 Pleonasm 1 Prolepsis 1 Antonomasia 1 Tautology (2) In realization figures of speech in surah Ar-rahman . ways in figures of speech in surah Ar-Rahman namely explicitly, comparing things, noun, repetition, synonym, denial, redundancy, substitution, and future. (3)The reason used figures of speech in surah Ar-rahman namely faith, laws of justice, man and jinn, hell and favors heaven.Key words: Figures of Speech, Ar-Rahman, Surah